Conscious and nonconscious thought: Insights from the neuroscience of decision-making - Michael N. Shadlen (Proceedings of the National Academy of Sciences, 2026)
Conscious thought is often treated as a special class of neural processing, distinct from the nonconscious computations that guide most behavior. Here I offer a different perspective, grounded in the neuroscience of decision-making. I argue that conscious thought arises not from a unique mechanism but from a distinctive use of neural representations already engaged in nonconscious thought. Nonconscious thoughts are structured as interrogations that yield provisional intentions—decision-like commitments that guide action or inquiry without entering awareness. Using examples from perceptual decision-making and neurophysiology, I suggest that such thoughts depend on persistent neural representations that encode not only potential actions but the questions that give them meaning. These knowledge states may also preserve source-sensitive structure that supports a minimal experiential organization even when they remain nonconscious. Conscious thought, on this account, emerges when such a state is reformatted for potential report to another mind, or to oneself, recruiting theory of mind and narrative structure and placing its content in a space presumed to be shared. This proposal identifies a tractable bridge from nonconscious decision mechanisms to phenomenal consciousness, thereby placing part of the hard problem within empirical reach.